2008
DOI: 10.1002/polb.21501
|View full text |Cite
|
Sign up to set email alerts
|

Rheology, electrical conductivity, and the phase behavior of cocontinuous PA6/ABS blends with MWNT: Correlating the aspect ratio of MWNT with the percolation threshold

Abstract: Multiwalled carbon nanotubes (purified, p-MWNT and $ NH 2 functionalized, f-MWNT) were melt-mixed with 50/50 cocontinuous blends of polyamide 6 (PA6) and acrylonitrile-butadiene-styrene in a conical twin-screw microcompounder to obtain conductive polymer blends utilizing the conceptual approach of double-percolation. The state of dispersion of the tubes was assessed using AC electrical conductivity measurements and melt-rheology. The rheological and the electrical percolation threshold was observed to be $ 1-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
80
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(86 citation statements)
references
References 34 publications
6
80
0
Order By: Relevance
“…But, covalent functionalization tends to negatively affect the physical and chemical integrity of CNTs. Strong acid treatments affects the geometry of the CNTs resulting in increased filler percolation thresholds [47]. Covalent treatments could also negatively affect the intrinsic electrical properties of the CNTs and have a profounding effect on the metallic characteristics of metallic CNTs [48].…”
Section: Modification Of Cnt Surfacementioning
confidence: 99%
“…But, covalent functionalization tends to negatively affect the physical and chemical integrity of CNTs. Strong acid treatments affects the geometry of the CNTs resulting in increased filler percolation thresholds [47]. Covalent treatments could also negatively affect the intrinsic electrical properties of the CNTs and have a profounding effect on the metallic characteristics of metallic CNTs [48].…”
Section: Modification Of Cnt Surfacementioning
confidence: 99%
“…Many studies were carried out to deal with the problem [11][12][13][14]. The design of double percolation structure in composites is one of the methods to reduce the percolation threshold of conductive fillers [15][16][17][18][19][20][21].The concept of double percolation was first proposed by Sumita et al [21] in immiscible blends that were filled with carbon black. Two requirements are needed to realize the double percolation structure in composites.…”
mentioning
confidence: 99%
“…length to width relation, is thought to play a large role in percolation threshold as it appears that conductive percolation paths are, in general, more easily set up when homogeneous dispersion of long and thin nanotubes is achieved. Several research studies have demonstrated that aspect ratio of MWCNTs is the main parameter in determining the conductive properties of polymer composites [32][33][34]. This has been fully supported by other studies, in which it was concluded that an increase in the aspect ratio of CNTs consistently implies an exponential decrease in percolation threshold of the composite [35,36].…”
mentioning
confidence: 88%